Warming drives a 'hummockification' of microbial communities associated with decomposing mycorrhizal fungal necromass in peatlands. Issue 6 (18th October 2021) - Maillard, François; Fernandez, Christopher W.; Mundra, Sunil; Heckman, Katherine A.; Kolka, Randall K.; Kauserud, Håvard; Kennedy, Peter G.
Summary: Dead fungal mycelium (necromass) represents a critical component of soil carbon (C) and nutrient cycles. Assessing how the microbial communities associated with decomposing fungal necromass change as global temperatures rise will help in determining how these belowground organic matter inputs contribute to ecosystem responses. In this study, we characterized the structure of bacterial and fungal communities associated with multiple types of decaying mycorrhizal fungal necromass incubated within mesh bags across a 9°C whole ecosystem temperature enhancement in a boreal peatland. We found major taxonomic and functional shifts in the microbial communities present on decaying mycorrhizal fungal necromass in response to warming. These changes were most pronounced in hollow microsites, which showed convergence towards the necromass‐associated microbial communities present in unwarmed hummocks. We also observed a high colonization of ericoid mycorrhizal fungal necromass by fungi from the same genera as the necromass. These results indicate that microbial communities associated with mycorrhizal fungal necromass decomposition are likely to change significantly with future climate warming, which may have strong impacts on soil biogeochemical cycles in peatlands. Additionally, the high enrichment of congeneric fungal decomposers on ericoid mycorrhizal necromass may help to explain the increase in ericoid shrub dominance in warming peatlands.